Doença da arranhadura do gato como causa de síndrome de Parinaud: relato de caso - Marcus Vinicius da Cruz Mendonça; Tiago de Hungria Cruz Conti; José Augusto de Oliveira Botelho; Vitória Roja de Oliveira (Residência Pediátrica)
INTRODUCTION: Cat Scratch Disease (CSD) in peditria is a disease of acute presentation, whose association with Parinauds syndrome is a rare event. OBJECTIVE: To report a case of a patient with CSD that progressed to Parinauds syndrome. CASE REPORT: Preschooler, female, arrives at the emergency room with a report of edema in the left eye 2 days ago.On physical examination, the affected region had edema, erythema with difficulty opening the ipsilateral eye associated with measured fever and headache that ceased with the use of analgesics. With hospitalization and prescription of antibiotic therapy, there was significant remission of the condition. CONCLUSION: Improving knowledge about the manifestations of infection by Bartonella hanselae and its complications is necessary for a better approach to patients.